Contribuições do pedagogo à prática pedagógica dos professores iniciantes: um estudo sobre a Educação Profissional Estadual de Ponta Grossa - PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
This research has as the object of study the contributions from pedagogues to beginner teachers’ pedagogical practices in Professional Education, in the State School System of Paraná. The research problem which guided the investigation in the research line of Teaching and Learning from the Post-Graduation Program – Masters and Doctoral Degrees of the State University of Ponta Grossa – was: What are the contributions from pedagogues to beginner teachers’ pedagogical practices in Professional Education, in the State School System in the city of Ponta Grossa? The general aim was to analyze the contributions from pedagogues to beginner teachers in the Professional Education area, in the State School System of Paraná, in search of improvement of pedagogical practices. The specific aims were: to identify the difficulties of pedagogues and beginner teachers in the area of Professional Education and to verify the pedagogues’ duties concerning the pedagogical guidance of those teachers. The following educational area authors were used as references: Nóvoa (1995), Giroux (1997), Sacristán (1999), Contreras (2002), Saviani (1989; 2002; 2009; 2013), Pimenta (1991; 2011), Libâneo (2009), Almeida e Placco (2012; 2016), Domingues (2009), Garcia (1999), Huberman (1995), Tardif (2002), Ferreira (2002), Brzezinski (2012), Kuenzer (1992; 1997), Romanowski (2012), Vázquez (2011), Perez Gomés (1998), Imbernón (2010) and Franco (2012). The research was based on the qualitative approach and the methodological procedures which were adopted, according to Trivinos (2010) were: questionnaires and semi-structured interviews with pedagogues from selected educational institutions, about the actions which were developed in order to improve the pedagogical practices of beginner teachers from the State School System of Paraná. The research included pedagogues who are working in ten (10) educational institutions which offer Professional Education in the city of Ponta Grossa. The pedagogues answered the first questionnaire as a group or individually. After that, twenty-three (23) questionnaires were handed in, to pedagogues who work directly in the Professional Education area, to be answered individually and, among those pedagogues, four (4) of them were selected to the semi-structured interview. The data analysis is based on Bardin (1995). The result of the research shows that the beginner teachers’ pedagogical practice in Professional Education has as a principle, the knowledge which was constructed during their academic education and life experience. The pedagogue must perform the role of mediator of the beginner teacher’s pedagogical practice, and his or her contributions must focus on discussions about methodologies, on directing critical reflections about teaching actions and on the articulation of knowledge, with continuous teacher development and in-service training.
Contributions from pedagogues to the pedagogical practice of beginner teachers: a study about State Professional Education in Ponta Grossa - PR
Keywords: Pedagogo; Prática pedagógica.; Professores iniciantes; Educação profissional; Pedagogue; Pedagogical practice; Beginner teachers; Professional education; CNPQ::CIENCIAS HUMANAS::PSICOLOGIA